The studies on one generator and one motor marine ship’s propulsion system control - Liu, Hongchao (2016)
The electric marine ships have been deployed for many years, but they are still facing a variety of problems and need to be perfected. Electricity makes it more efficient than consuming raw energy resources like gasoline. There are many rectifiers and inverters which are composed of conventional thyristors and diodes causing inherent drawbacks, such as harmonics and reactive power, which contribute to the power system pollution on the marine ships. In this thesis, a one generator and one motor marine ship’s propulsion system is studied for simplicity and efficiency. In my research, a one generator and one motor marine ship power system model is set up in which a new control method of PWM rectifier based on the power ripple minimization is introduced and applied. It will reduce the power loss and improve the power quality of the marine ship’s power system. The marine ship’s propulsion motor control is also demonstrated and the Fuzzy-PID controller is applied. What’s more, an energy storage system is designed to stabilize the one generator and one motor marine ship’s power system and store energy when it is necessary. My main contributions in this thesis can be summarized as follows: 1. Modelling of the one generator and one motor marine propulsion system. 2. The generator model and its simulation in which a rectifier based on power ripple minimization DPC control strategy is applied. 3. The design of a double closed loop control system of DC motor and its improvement with Fuzzy-PID control. 4. An energy storage system is designed and applied in the one generator and one motor marine propulsion system.